The Use of Pledges to Build and Sustain Commitment in Distribution Channels - Anderson, Erin; Weitz, Barton (Journal of Marketing Research, 1992)
Commitment in channel relationships is modeled as a function of (1) each party's perception of the other party's commitment, (2) self-reported and perceived pledges (idiosyncratic investments and contractual terms) made by each party, and (3) other factors such as communication level, reputation, and relationship history. A dyadic model represented by a simultaneous equation system is estimated with data from 378 pairs of manufacturers and industrial distributors. The results indicate that one type of pledge, idiosyncratic investments, has a strong effect on the commitment of both parties to the relationship. In addition, each party's commitment is affected by the perceived commitment of the other party. Finally, idiosyncratic investments signal commitment, affecting each party's perceptions of the other party's commitment.